Role of Nano Materials in Improving Compressive Strength of Bio-Foamed Concrete Bricks: Towards Green Concrete Production - Alshalif, Abdullah Faisal; Mohammed Ali Mansour; Muhammad Mirza Sabarudin; Ibrahim Mohammed Nasser; Ali Gamil Al-Halhali (Journal of Structural Monitoring and Built Environment, 2025)
This study explores the enhancement of compressive strength in bio-foamed concrete through the integration of nanomaterials such as nano rice husk ash (NRHA), nano eggshell powder (NESP), nano coffee grounds (NUCG) as cement replacements, alongside the bacterial agent. By utilizing agricultural and food waste, this research aims to investigate the compressive strength of bio-foamed concrete brick (B-FCB) at 28 days using screening stage method. The nano materials enhanced the compressive strength of the B-FCB. The optimal replacement materials for the maximum compressive strength were 1% NRHA, 1% NUCG, and 5% NESP, combined with Bacillus tequilensis at a concentration of 3×105 cells/ml. The empirical modelling indicated that Bacillus tequilensis and ESP have a significant effect on the compressive strength of B-FCB. Incorporating nanosized agro-industrial wastes into B-FCB improves mechanical performance while reducing the environmental impact of accumulated wastes.